Analysis of Chemistry Podcast Implementation in Learning Hydrocarbons and Petroleum for Inclusive Students - Pingki Wahyu Septianing; Sulistyo Saputro; Lina Mahardiani; Nurma Yunita Indriyanti; Icha Desti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
This research aims to conduct a feasibility analysis of a chemistry podcast, referred to here as “PodChem,” and to examine the impact of PodChem on learning hydrocarbons and petroleum. This study employs a pre-experimental method. The podcast media were developed using Anchor software and evaluated through a survey using a podcast media assessment questionnaire. The evaluation was carried out by lecturers as validators and students as podcast users. The assessed aspects include content, functionality, and appearance as complementary media in learning hydrocarbons and petroleum. The results indicate that the chemistry podcast PodChem was successfully produced using Anchor software. The findings suggest that PodChem is valid and suitable for educational use. The audio quality produced using Anchor is clear, and its accessibility is broad. Additionally, students reported that the content is relevant and enhances their understanding of the subject matter. Most students also found the podcast to be easily accessible and effective in conveying the concept. In terms of appearance, students agreed that the podcast title is engaging, the delivery is captivating, and the duration is appropriate. The implementation of PodChem in chemistry learning received positive feedback from students, with the majority accepting the use of podcast media in the classroom. Furthermore, 88.9% of respondents expressed a desire for podcasts to be used as complementary media in future learning, as they found podcasts to be more interesting, insightful, and easy to understand. These conclusions are supported by the results of student questionnaires and the assessment of assignments conducted by teachers in class.